Eliminating mother-to-child transmission of hepatitis B virus: practice and progress in Baoan, a national pilot district of China - Ya-Li Luo; Shuang Gao; Quan-Fu Zhang; Xian Liu; Ding-Yan Lv; Jia-Hong Chen; Wei Wang (BMC, 2024)
Abstract Background While mother-to-child transmission (MTCT) of hepatitis B virus (HBV) remains a significant challenge in China, research investigating the effectiveness of the September 2017 pilot program to eliminate MTCT of HIV, syphilis, and HBV is limited. Baoan district, which has a higher-than-average rate of hepatitis B infection among pregnant women and strong support from the government, was one of six national pilot districts selected for the program. Therefore, this study aims to assess the progress and implementation of the elimination of MTCT of HBV in Baoan district over a period of 5 years. Methods Data was collected from the national information system for the prevention of MTCT, registration forms, and follow-up forms of pregnant women and their live births from 2018 to 2022. Joinpoint models were used to analyze changing trends over time, calculating annual percentage change (APC) and the corresponding 95% confidence interval (95%CI). Multivariate logistic regression models were used to analyze risk factors for HBV MTCT. Results From 2018 to 2022, the coverage of HBV screening during pregnancy increased from 98.29 to 99.55% (APC = 0.30, P = 0.012). The coverage of HBV early screening within 13 gestational weeks increased from 40.76 to 86.42% (APC = 18.88, P = 0.033). The prevalence of maternal HBV infection declined by an APC of − 3.50 (95% CI -6.28 ~ − 0.63). The coverage of antiviral therapy among high-risk pregnant women increased from 63.59 to 90.04% (APC = 11.90, P = 0.031). Coverage for timely administration of hepatitis B immunoglobulin, hepatitis B birth dose vaccine, and three-dose hepatitis B vaccination remained consistently above 97.50%. The coverage of post-vaccination serological testing (PVST) in high-risk infants was 56.15% (1352/2408), and the MTCT rate of HBV was 0.18%. Mothers with high-school education or below (OR = 3.76, 95% CI 1.04 ~ 13.60, P = 0.04) and hepatitis B e antigen (HBeAg) positivity (OR = 18.89, 95% CI 1.98 ~ 18.50, P = 0.01) had increased MTCT risk. Conclusions The implementation of comprehensive prevention strategies in Baoan district, including screening, treatment, and immunoprophylaxis, has proven effective in maintaining the MTCT of HBV at an extremely low level. However, it remains crucial to raise public awareness, specifically on the importance of improving the coverage of PVST for infants exposed to HBV.